Patient satisfaction with dialysis services provided across different providers in Saudi Arabia - Monshi, Sarah S.; Alamri, Hatoon M.; Almuaddi, Afnan M.; Almutairi, Fatemah M.; Aljishi, Hala R.; Alfaki, Khulud A.; AlTurki, Maram S.; Saqah, Rayyan M.; Aldossary, Mohammed S. (Frontiers in Nephrology, 2026)
ObjectivesThis study aimed to evaluate patient satisfaction with dialysis services provided across different healthcare sectors in Saudi Arabia, including governmental and private facilities, and to identify key determinants influencing satisfaction levels.MethodsA cross-sectional observational study was conducted using secondary data from dialysis patients attending Ministry of Health, Diaverum, and DaVita facilities between January and December 2023. Patient satisfaction data were collected through the Press Ganey survey, a validated instrument assessing six domains: registration, care, dialysis, pharmacy, personal issues, and personal experience. Descriptive statistics summarized patient demographics and satisfaction scores, while regression analysis identified factors associated with satisfaction.ResultsA total of 5,472 patients were included, with an overall satisfaction score of 89.84 ± 14.25. The mean satisfaction score was highest in the personal experience domain (91.39 ± 17.02) and lowest in the dialysis domain (88.45 ± 18.65). Private facilities had statistically significant higher satisfaction scores (90.41 ± 13.31) compared to governmental hospitals (88.57 ± 16.08). Females reported significantly higher satisfaction than males (91.96 ± 12.15 vs. 88.91 ± 14.60), respectively. Pediatric patients demonstrated significantly higher satisfaction (age ≤18 years: 93.80 ± 11.42) compared to young adults (age = 19–29 years: 89.18 ± 14.62). Regional differences were observed, with the Southern region reporting the highest satisfaction (91.37 ± 14.18) and the Eastern region the lowest (88.60 ± 15.59). Regression analysis identified gender (B = 2.943, 95% CI [2.165, 3.722], p < 0.001) and facility type (B = 1.108, 95% CI [0.243, 1.973], p = 0.012) as significant predictors of satisfaction.ConclusionPatient satisfaction with dialysis services in Saudi Arabia is generally high, with statistically significant but modest differences across regions, facility types, age groups, and genders. Improving dialysis-related education, addressing regional disparities, and enhancing patient-centered care, particularly in governmental facilities, could further optimize satisfaction outcomes.